2021
DOI: 10.1007/s12155-021-10328-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Genetic Parameters of Flowering Time-Related Traits in a Miscanthus sinensis Population Tested with a Staggered-Start Design

Abstract: There is a growing interest in the cultivation of miscanthus on marginal land, but biomass yields are much lower there than on good farming land. Therefore, understanding what causes such instability is of primary interest for breeding laterowering but stable miscanthus genotypes. Our objectives were to estimate the genetic parameters -genetic variance and genetic heritability-and genetic correlations for owering-time-related traits in a biparental Miscanthus sinensis diploid population, and to divide the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…More and more studies have demonstrated that plant age strongly influences plant growth and growing seasons and that climate effects result in lower genetic parameters than age effects (Hou et al, 2022). However, the conflation of plant age and growing season effects on perennial crops in many studies increases uncertainty and the possibility of drawing erroneous conclusions.…”
mentioning
confidence: 99%
“…More and more studies have demonstrated that plant age strongly influences plant growth and growing seasons and that climate effects result in lower genetic parameters than age effects (Hou et al, 2022). However, the conflation of plant age and growing season effects on perennial crops in many studies increases uncertainty and the possibility of drawing erroneous conclusions.…”
mentioning
confidence: 99%